Hikmat dalam Kitab Amsal: Integrasi Karakter Wanita Cakap, Peringatan Moral, dan Pemeliharaan Jalan Kebijaksanaan - Yanto Sandy Tjang; Mayong Andreas Acin (JURNAL PASTORAL KATEKETIK, 2026)
This study explores the principles of wisdom in the Book of Proverbs, with a focus on the integration of moral, spiritual, and practical dimensions in human life. The study aims to identify the characteristics of the capable woman in Proverbs 31, analyze the central themes in Proverbs 1–9 related to preventive warnings, and examine the maintenance of the paths of wisdom in Proverbs 8 as a practical guide for ethical and prudent living. The research employs a qualitative-exegetical approach based on library studies, with the Book of Proverbs as the primary source and secondary sources including theological literature, contemporary biblical commentaries, and studies on wisdom literature. Data analysis was conducted thematically and hermeneutically through critical reading, contextualization, and textual interpretation. The findings indicate that the capable woman exemplifies an integration of piety, diligence, integrity, and social care through concrete actions, serving as a model of the harmonious integration of moral, spiritual, and practical principles. Warnings to avoid wicked companions and married women underscore the importance of moral awareness, selective social engagement, and social responsibility. The encouragement to pursue wisdom and maintain the paths of wisdom emphasizes character development, obedience to God, and consistent ethical practice. Overall, the study affirms that Proverbs presents a holistic moral framework integrating faith, ethics, and practical action, offering guidance for wise, ethical, and sustainable living.